ChemInform Abstract: When NHC Ligands Make a Difference in Gold Catalysis. Issue 31 (5th August 2014) - Gatineau, David; Goddard, Jean‐Philippe; Mouries‐Mansuy, Virginie; Fensterbank, Louis
Abstract Review: [51 refs.